Impact of tidal level fluctuations on the structural behaviour of a segmental tunnel lining. (April 2017) - Schotte, Ken; Nagy, Wim; Nuttens, Timothy; De Wulf, Alain; Van Bogaert, Philippe; De Backer, Hans
Highlights: The Liefkenshoek tunnel moves up and down with the tides of River Scheldt. At high tide, the tunnel level is 10 mm lower compared to the situation at low tide. Monitoring results were compared with FE-calculations to identify the cause. The displacements are due to the elastic response of the impermeable Boom clay layer. The clay is not able to shield the lining from the fluctuating water pressures.